Developing Digital Role Play-Based Educational Learning Media through the TikTok Platform to Improve Students' Internalization of Character - Dayung Ramadhan; Bagas Mukti Nahrowi; Ali Ghufron (FITK UIN Walisongo Semarang, 2026)
This study aims to develop a digital role-play-based educational learning media through the TikTok platform to improve students' internalization of character values. This study uses the Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques were carried out through observation, interviews, and questionnaires with a Likert scale. The results of the study indicate that the developed media has a very high level of feasibility, with an average validation score of 4.5 from media experts and 4.6 from material experts, categorized as